2008
DOI: 10.1108/13639510810895768
|View full text |Cite
|
Sign up to set email alerts
|

Pricing police services: theory and practice

Abstract: PurposeThe purpose of the paper is to present and test a particular theory of pricing of police services.Design/methodology/approachA theory of police pricing was developed, then tested using data collected from a mail survey of Chiefs of Police in Pennsylvania.FindingsPricing practices vary considerably among police departments. There appears to be no underlying theory in the practice of pricing of police services.Research limitations/implicationsResearch was limited to one state in the USA and for a limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Existing quantitative performance measures have been established upon the old policing paradigm of response policing and enforcement activity (Maguire and Tim, 2006;Collier et al, 2004). Often effective crime prevention and disruption either have a neutral or negative effect on organisational performance measurements for LEAs (Talaga and Tucci, 2008). This problem is even more pronounced for strategic law enforcement intelligence which is often unable to track outcomes to specific police activity recorded by traditional law enforcement performance measures.…”
Section: Capability and Performance Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Existing quantitative performance measures have been established upon the old policing paradigm of response policing and enforcement activity (Maguire and Tim, 2006;Collier et al, 2004). Often effective crime prevention and disruption either have a neutral or negative effect on organisational performance measurements for LEAs (Talaga and Tucci, 2008). This problem is even more pronounced for strategic law enforcement intelligence which is often unable to track outcomes to specific police activity recorded by traditional law enforcement performance measures.…”
Section: Capability and Performance Measuresmentioning
confidence: 98%
“…Law enforcement struggles to develop meaningful performance measures to evidence efficient and effective outcomes on crime (Talaga and Tucci, 2008). Existing quantitative performance measures have been established upon the old policing paradigm of response policing and enforcement activity (Maguire and Tim, 2006;Collier et al, 2004).…”
Section: Capability and Performance Measuresmentioning
confidence: 99%
“…For example, organizational commitment is associated with several variables of organizational outcomes, including absenteeism (e.g., Jacobsen and Fjeldbraaten, 2020 ), turnover intention (e.g., de la Torre-Ruiz et al, 2019 ), work satisfaction (e.g., Massoudi et al, 2020 ), person–organization value fit (Zhao et al, 2021 ), and innovation performance (e.g., Iqbal et al, 2021 ). For non-profit service providers such as immigration agencies, fire agencies, and public libraries, they essentially provide free service to their clients (Talaga, 2008 ) due to their altruistic nature. Relevant studies had shown that the organizational commitment and OCB could improve the organizational performance, especially the reveal of service quality (Heydari and Lai, 2019 ).…”
Section: Introductionmentioning
confidence: 99%